2022
DOI: 10.3389/fnut.2022.939454
|View full text |Cite
|
Sign up to set email alerts
|

Information disorder and organic food purchasing behavior: A moderated mediation model

Abstract: On the one hand, fast social media and internet evolution has brought opportunities to the development of the organic food industry. On the other hand, the excessive utilization of social media and internet has also exerted some negative effects on consumers in terms of information disorder and hindered the industrial progression of organic foods. This study aimed to probe into the relationships between organic food information uncertainty, information search anxiety, information overload and purchase behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…In comparison, H4c, proposing a positive association of symbolic-driven pleasure with purchase intention, was not supported. This could be attributed to the fact that organic food is not yet mainstream in China, where consumers do not place a high emphasis on organic food (Zheng and Cao, 2022). Moreover, Hyldelund et al (2021) confirmed that in addition to sensory-driven pleasure being considered as the main driving force for consumers to purchase a specific product under different cultural backgrounds, whether other dimensions of food pleasure play a role in purchasing decision depends on a specific product and consumer groups.…”
Section: Moderation Of Functionality Trust (Ft) On the Relationship B...mentioning
confidence: 86%
See 3 more Smart Citations
“…In comparison, H4c, proposing a positive association of symbolic-driven pleasure with purchase intention, was not supported. This could be attributed to the fact that organic food is not yet mainstream in China, where consumers do not place a high emphasis on organic food (Zheng and Cao, 2022). Moreover, Hyldelund et al (2021) confirmed that in addition to sensory-driven pleasure being considered as the main driving force for consumers to purchase a specific product under different cultural backgrounds, whether other dimensions of food pleasure play a role in purchasing decision depends on a specific product and consumer groups.…”
Section: Moderation Of Functionality Trust (Ft) On the Relationship B...mentioning
confidence: 86%
“…In comparison, H4c, proposing a positive association of symbolic-driven pleasure with purchase intention, was not supported. This could be attributed to the fact that organic food is not yet mainstream in China, where consumers do not place a high emphasis on organic food (Zheng and Cao, 2022). Moreover, Hyldelund et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high purchasing pattern is determined by an increased level of consumer awareness of safe food and health concerns ( 5 , 6 ). The demand for nutritious organic food is based on its quality ( 7 , 8 ). While the demand for organic food is increasing, the popularity of organic food is not widespread and consumers’ perception of organic food is varied ( 9 ).…”
Section: Introductionmentioning
confidence: 99%